Electro-thermal Coupling Model for Radial Temperature and Electric Field Distribution Computation and Experimental Research of 550kV RIP AC Oil-gas Bushings. Issue 1 (July 2021) - Shiling, Zhang; Wei, Song; Huaxia, Yang
Abstract: The condenser of 550kV RIP oil-gas bushings is in the solid structure of resin-epoxy impregnated paper(RIP), which has large difference with the oil-immersed one (OIP). Oil-gas bushings has compact configuration and heat conduction condition is harsh, while temperature distribution has direct relationship with bushings' long-term stable operation performance, so it's essential to carry out research in radial temperature within condenser during production of RIP oil-gas bushing prototype. In this paper, radial temperature distribution principle of bushing condenser under linear material conditions has been summarized by building electrothermal coupling theoretical model of bushing condenser. The model has been generalized by electro-thermal coupling finite element mode under nonlinear material conditions, and electrothermal coupling iterative computation process has also been proposed, then experimental measurement study in local temperature points of bushing condenser has been carried out. The study shows that plate model has advantages of high accuracy and simple form in calculating radial temperature distribution of bushing condenser; the hot-spot temperature of 550kV RIP oil-gas bushings is about 95°C which appears near the center conductor; radial temperature of bushings under nonlinear material conditions is lower than that under linear material conditions and the thermal breakdown voltage of condenser under rated current is 538kV which is higher than the maximum operation phase voltage. This paper provides theoretical foundation for radial temperature computation within RIP bushing condenser and has some reference value for the design of HVAC RIP bushings.